Almost (United States. McCullough Entertainment L.L.C., 1990)
Wendy (Rosanna Arquette) is a bored timid housewife in a seemingly fizzled marriage. She longs for the adventure, and more importantly, the sensuality she finds within the pages of her romance novels. But, it becomes evident owing to a series of ironies, accidents and misadventures that even Tually causes Wendy and her lovable doofus husband, Ronnie (Bruce Pence of the mad max movies) to see what went wrong and to remember what attracted them to each other in the first place
Keywords: Romantic Comedy